Dumping social trabalhista, as empresas trabalhistas e os direitos humanos - Cavalcante, Rodrigo Arantes (2023)
Bearing in mind the conflict between capital and work, considering the need for economic growth of companies and the still existing practices of social dumping in search of greater profitability, it is necessary to rethink work and employment relations within transnational companies, aiming at sustainable economic growth in the labor area, respecting human rights, the global pact, and the sustainable development goals indicated by the UN in the 2030 agenda, with better business management, based on humanist capitalism, in this approach, which in addition to reducing costs as to labor liabilities, makes the company more productive and profitable, contributing to the country's economic growth. The objective of this project is to identify the main actions that occur in social dumping practices, in particular slave-like work, overtime work, irregular outsourcing, and other behaviors that typify social harm, through the collection of public data in judged reported, as well as listing means of effecting human rights to such issues, enabling sustainable economic growth for transnationals, and even in case of disrespect for human rights, studying what are the possible mechanisms of internal and external control, through a bibliographical review.